World Development Indicators 2002 - World Bank (World Development Indicators, 2002)
This is the sixth edition of the World Development Indicators in its current format, the 25th since the World Bank began publishing a comprehensive set of development indicators. It begins with a report on the Millennium Development Goals, which set specific, measurable targets for development in the early 21st century. To measure progress, results have to be measured and for that good statistics are needed. Most of the statistics in this report are produced by national statistical agencies. The World Bank supports investments to improve the quality of statistics through a wide range of efforts. The Bank is a member of the Partnership in Statistics for the 21st Century, the Bank is working closely with its development partners to raise awareness of the need for the value of good statistics and to increase the resources available for statistical capacity building in developing countries. The World Bank Institute is offering training programs to build statistical capacity building in the countries preparing poverty reduction strategies. Through the International Comparison Programme (ICP), the Bank is working to improve the quality of data for comparing standards of living across countries. The Bank has established a trust fund for building statistical capacity